Alcohol solution strength preference predicts compulsive‐like drinking behavior in rats. (11th August 2022) - Foo, Jerome C.; Meinhardt, Marcus W.; Skorodumov, Ivan; Spanagel, Rainer
Abstract: Background: Understanding compulsive drinking behavior is key to improving outcomes in the treatment of addiction. In the present study, we investigated compulsive‐like drinking in alcohol‐addicted rats using the alcohol deprivation effect (ADE) model of relapse behavior, which involves repeated deprivation and reintroduction phases; the latter approximate relapse. Methods: High‐resolution longitudinal drinking and locomotor data were measured while rats ( n  = 30) underwent a four‐bottle (water, 5%, 10%, 20% alcohol v/v) free‐choice ADE paradigm. Alcohol bottles were adulterated with the bitter compound quinine during a reintroduction phase to test for compulsive behavior. We characterized how drinking and locomotor behavior during ADE + quinine differed from a regular ADE and how, at the individual level, behavioral parameters extracted from the regular ADE related to compulsive‐like drinking. Associations of drinking with locomotor activity were also examined. Results: In the ADE with quinine, we observed reduced consumption of alcohol and a shift to preference for stronger alcohol. Quinine acted by decreasing both the access size and frequency of drinking of 5% alcohol while increasing the frequency of consumption of 20% alcohol. Preference for higher alcohol concentrations prior to the quinine challenge was associated with greater compulsive‐like drinking behavior; higher baseline consumption of 20% alcohol correlated with more drinking of quinine‐adulterated solutions while high frequency and amount of 5% alcohol consumption at baseline were correlated with being more strongly affected by quinine. Associations between locomotor activity and drinking behavior were observed at the hourly level. These associations reflected changing preferences across experimental phases. Conclusion: Drinking patterns, and specifically solution preference, may offer insights into the presentation of compulsive‐like drinking. The findings provide a preclinical basis for observations from epidemiological studies that link higher risk and burden of alcohol‐related disease to stronger alcohol concentrations and encourage further translational studies to better understand the underlying mechanisms. Abstract : Understanding the loss of control can improve outcomes in addiction treatment. To examine compulsive‐like drinking, the present study assessed longitudinal drinking behaviour while employing an animal model of relapse including a quinine challenge; addicted rats continue to drink even when the taste of alcohol is made aversive. Findings characterize the response to quinine and suggest a potential link between earlier drinking patterns and eventual compulsive‐like drinking.